Association of anemia and platelet activation with necrotizing enterocolitis with or without sepsis among low birth weight neonates: a case–control study - Jiang, Zhou; Ye, Guangyong; Zhang, Songying; Zhang, Long (Frontiers in Pediatrics, 2023)
Background This study aims to evaluate the value of the proportion of large platelets (PLCR) and platelet crit (PCT) in predicting necrotizing enterocolitis (NEC) in low birth weight (LBW) neonates. Methods A total of 155 LBW (<2,500 g) neonates with NEC, who were admitted to the neonatal intensive care unit (NICU) of the hospital from January 1, 2017, to November 30, 2019, were included in the case group. According to the 1:3 case–control study design, a total of 465 LBW neonates without NEC (three for each LBW neonate with NEC), who were admitted to the NICU and born ≤24 h before or after the birth of the subjects, were included in the control group. Results During the study period, a total of 6,946 LBW neonates were born, of which 155 had NEC, including 92 who also had sepsis. Neonatal sepsis was the most important risk factor and confounding factor for NEC in LBW neonates. Further stratified analysis showed that in LBW neonates without sepsis, anemia [P = 0.001, odds ratio (OR) = 4.367, 95% confidence interval (CI): 1.853–10.291], high PLCR (P < 0.001, OR = 2.222, 95% CI: 1.633–3.023), and high PCT (P = 0.024, OR = 1.368, 95% CI: 1.042–1.795) increased the risk of NEC and the receiver operating characteristic curve area of PLCR, sensitivity, specificity, and cutoff value were 0.739, 0.770, 0.610, and 33.55, respectively. Conclusions The results showed that 2/100 LBW neonates were at risk for NEC, and the stratified analysis of the confounding factors of sepsis identified the risk factors of NEC in LBW neonates. This study first reported the significance of PLCR in the early prediction of NEC occurrence in LBW neonates without sepsis.